Advances in space quantum communications. Issue 4 (19th July 2021) - Sidhu, Jasminder S.; Joshi, Siddarth K.; Gündoğan, Mustafa; Brougham, Thomas; Lowndes, David; Mazzarella, Luca; Krutzik, Markus; Mohapatra, Sonali; Dequal, Daniele; Vallone, Giuseppe; Villoresi, Paolo; Ling, Alexander; et al.
Abstract: Concerted efforts are underway to establish an infrastructure for a global quantum Internet to realise a spectrum of quantum technologies. This will enable more precise sensors, secure communications, and faster data processing. Quantum communications are a front‐runner with quantum networks already implemented in several metropolitan areas. A number of recent proposals have modelled the use of space segments to overcome range limitations of purely terrestrial networks. Rapid progress in the design of quantum devices have enabled their deployment in space for in‐orbit demonstrations. We review developments in this emerging area of space‐based quantum technologies and provide a roadmap of key milestones towards a complete, global quantum networked landscape. Small satellites hold increasing promise to provide a cost effective coverage required to realise the quantum Internet. The state of art in small satellite missions is reviewed and the most current in‐field demonstrations of quantum cryptography are collated. The important challenges in space quantum technologies that must be overcome and recent efforts to mitigate their effects are summarised. A perspective on future developments that would improve the performance of space quantum communications is included. The authors conclude with a discussion on fundamental physics experiments that could take advantage of a global, space‐based quantum network.